THE INFLUENCE OF E-COMMERCE AND SUPPLY CHAIN MANAGEMENT ON THE GROWTH OF MSME INCOME IN GORONTALO (Jurnal Ilmu Manajemen dan Bisnis, 2025)
The development of digital technology has driven a transformation in MSME business models, particularly in the use of e-commerce and supply chain management to increase income. This phenomenon highlights the need for empirical studies on the strategic role of these two variables in supporting MSME growth. This study aims to analyze the effect of e-commerce and supply chain management on the income growth of MSMEs. A quantitative research approach was used with Structural Equation Modeling–Partial Least Squares (SEM-PLS) as the analytical method, involving a sample of 66 MSMEs. The results showed that e-commerce has a positive and significant effect on MSME income growth, with a T-Statistic value of 3.210 and a P-Value of 0.001. Similarly, supply chain management also has a positive and significant effect, with a T-Statistic value of 7.497 and a P-Value of 0.000. These findings indicate that digital technology integration in marketing and efficient supply chain operations are key factors in enhancing income and ensuring MSME sustainability. Therefore, it is essential for MSME actors to strengthen their digital and managerial capabilities through appropriate training and infrastructure support from the government and business partners.